O desenvolvimento de um laboratório virtual para o ensino da 1ª Lei de Ohm utilizando o GeoGebra - Guerreiro, Luis Gustavo Jayme (2020)
With the potential of using Information and Communication Technologies (TIC) in Physics Education, it was decided to develop a Virtual Learning Laboratory (LVA) using the GeoGebra software and five application scripts in order to provide opportunities for the study of the 1ª Law Ohm's and resistor associations in high school (EM). In addition to the development of LVA and the application scripts of the same, this work also sought to analyze the benefits and strategies for using LVA. support of a theoretical framework it was decided to guide the applications in David Ausubel's theory of Significant and prove that the LVA applied correctly and with the students' pre-disposition this tool can be potentially significant. The results obtained here were of qualitative analysis and refer to the teacher's perceptions during the applications when compared with his previous experiences of teaching the 1st Ohm's Law prior to teaching associations without using the Virtual Learning Laboratory